Identifying Problems Challenging the Academic Performance of Students in Physics at Preparatory Schools in Arsi Zone - Nigusu Tesfaye (ASTU, 2018)
This study was conducted to identify problems challenging the academic performance of students in some selected preparatory schools in Arsi zone. The respondents for this study were 110 natural science preparatory school students, physics teachers, physics department heads and school principals. The samples of the study were selected through cluster sampling method and ratios were calculated for the strata. The instruments used to collect data were the questionnaire, semi-structured interview, document analysis and observations for information gathering about different factors relating to academic performance of students. The data gathered through closed-ended items were coded, tabulated and analyzed using descriptive statistics such as frequency, mean and standard deviation, whereas, the additional data gained from semi-structured interview, documents and observations were also coded, categorized and identified thematically in order to approve or disapprove the quantitative data. SPSS were applied to investigate the effect of different factors on students’ achievement. The results of the study revealed that students back ground, entry behavior, attitudes to the subject , inadequate use of resource in the teaching and learning process ,students characteristics, negative socio-cultural factors, parents’ and per influences were the main causes of the students' persistent poor performance in physics in Arsi zone preparatory schools. Based on the findings, it is recommended that the Ministry of Education through its various agents should, among other things, enhance supervision of entry behavior of students in preparatory schools, increase the amount allocated for tuition and release the funds in good time to enable prompt acquisition of laboratories and learning materials. Motivational talks by physics professionals and Observation of physics-based industries as a way of motivating the students to help change negative attitude and to build positive attitude of students towards the subject. School managements, in conjunction with other stakeholders, should enhance students and teacher motivation and provide more and better teaching and learning facilities to enable a more conducive environment for learning. Finally, physics teachers must motivate the students to perform better in the subject.
(The case of Bekoji, Hetosa, Tiyo and Sagure Preparatory Schools)